Prevention of Normal Escherichia Coli Flora Resistance by Using Probiotics in Combination Antibiotic-Induced Mice - Iskandar, Fildzah Febriana; Ruliatna, Etty Fitria; Kusnaningrum, Yuyun (CV. Publikasi Indonesia, 2025)
The indiscriminate use of broad-spectrum antibiotics can cause gut microbiota dysbiosis and select for resistant bacteria, including commensal Escherichia coli. Probiotics such as Lactobacillus plantarum and Saccharomyces boulardii are believed to restore microbiota balance and prevent antibiotic resistance. This study aimed to evaluate the effectiveness of L. plantarum, S. boulardii, and their combination in preventing antibiotic resistance in commensal E. coli in the intestines of Wistar rats induced with a combination of antibiotics. An experimental post-test control group design was conducted using 25 male Wistar rats divided into five groups: negative control, positive control (antibiotics only), and three treatment groups (antibiotics + L. plantarum, antibiotics + S. boulardii, antibiotics + both). The resistance profile of E. coli from fecal samples was analyzed on days 7 and 14 using the Kirby-Bauer method against ceftazidime, meropenem, ciprofloxacin, gentamicin, and trimethoprim-sulfamethoxazole. Statistical analysis used Independent Sample T-Test (p<0.05). The positive control group showed a significant reduction in antibiotic inhibition zones, indicating increased E. coli resistance. In the L. plantarum (alone or combination) groups, no E. coli growth was found in fecal cultures. The S. boulardii group showed significantly higher antibiotic sensitivity compared to the positive control (p<0.05). Conclusion: Administration of probiotics, particularly L. plantarum and its combination with S. boulardii, was effective in preventing antibiotic resistance in commensal E. coli after induction with broad-spectrum antibiotics in rats. These findings support the use of probiotics as adjuncts to antibiotic therapy to suppress resistance development at the gut microbiota level.